2020
DOI: 10.3748/wjg.v26.i38.5784
|View full text |Cite
|
Sign up to set email alerts
|

Role of artificial intelligence in the diagnosis of oesophageal neoplasia: 2020 an endoscopic odyssey

Abstract: The past decade has seen significant advances in endoscopic imaging and optical enhancements to aid early diagnosis. There is still a treatment gap due to the underdiagnosis of lesions of the oesophagus. Computer aided diagnosis may play an important role in the coming years in providing an adjunct to endoscopists in the early detection and diagnosis of early oesophageal cancers, therefore curative endoscopic therapy can be offered. Research in this area of artificial intelligence is expanding and the future l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…AI systems are being used (eg, I-scan and CADDIE) in BO to find dysplasia current methods miss. [41][42][43] Lesion detection in BO is notoriously challenging for the uninitiated, and AI may provide some guidance; however, it requires a skilled workforce to use and interpret the signals from AI devices and to counsel patients about the potential limitations as responsibility remains with the operator. 44 Machine learning tools could help to teach a dedicated workforce how to detect dysplasia.…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%
“…AI systems are being used (eg, I-scan and CADDIE) in BO to find dysplasia current methods miss. [41][42][43] Lesion detection in BO is notoriously challenging for the uninitiated, and AI may provide some guidance; however, it requires a skilled workforce to use and interpret the signals from AI devices and to counsel patients about the potential limitations as responsibility remains with the operator. 44 Machine learning tools could help to teach a dedicated workforce how to detect dysplasia.…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%
“… 23 IPCL is commonly identified using chromoendoscopy or advanced endoscopic imaging with NBI. 24 The precise classification in real-time is subjective, inconsistent and reliant on experienced endoscopists. With the increasing volume of work in endoscopy, AI models have been developed to improve the diagnostic accuracy of IPCLs and possibly mitigate the need for expert endoscopists.…”
Section: Resultsmentioning
confidence: 99%
“…4 Despite advances in endoscopic imaging, BE dysplasia is still missed. 5 A metaanalysis showed that amongst adults with NDBE at index endoscopy and prolonged follow up, 25% of EAC's are diagnosed within a year of the index procedure. They were classified as a missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is time consuming and may suffer from sampling error 3 and poor compliance 4 . Despite advances in endoscopic imaging, BE dysplasia is still missed 5 . A meta‐analysis showed that amongst adults with NDBE at index endoscopy and prolonged follow up, 25% of EAC's are diagnosed within a year of the index procedure.…”
Section: Introductionmentioning
confidence: 99%